2010
DOI: 10.1080/02607470903462222
|View full text |Cite
|
Sign up to set email alerts
|

Closing the gap between the theory and practice of teaching: implications for teacher education programmes in Hong Kong

Abstract: The gap between the theory and practice of teaching is an issue of concern in teacher education. Although researching this gap is not new, few studies have been conducted in Hong Kong. It is worth investigating the contemporary Asian models of teacher education that can provide reference to the international literature. This paper examines this theory-practice gap by reporting a study that researched the inconsistencies between student teachers' best teaching strategies and their most commonly employed ones. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(94 citation statements)
references
References 32 publications
4
87
1
2
Order By: Relevance
“…Mattheoudakis, 2007;Peacock, 2001;Tabachnick & Zeichner, 2003;Wong, 2010), the findings of this study are consistent with studies confirming that these beliefs are variably permeable to change (Brandenburg, 2008;Cabaroglu & Roberts, 2000;Calderhead & Robson, 1991;Cheng, Cheng, & Tang, 2010;Misrohmawati, 2016) in different individuals. In such development processes, the role of the associate teacher and mentor and teacher training program in providing cognitive support and guidance should not be overlooked.…”
Section: Discussionsupporting
confidence: 80%
“…Mattheoudakis, 2007;Peacock, 2001;Tabachnick & Zeichner, 2003;Wong, 2010), the findings of this study are consistent with studies confirming that these beliefs are variably permeable to change (Brandenburg, 2008;Cabaroglu & Roberts, 2000;Calderhead & Robson, 1991;Cheng, Cheng, & Tang, 2010;Misrohmawati, 2016) in different individuals. In such development processes, the role of the associate teacher and mentor and teacher training program in providing cognitive support and guidance should not be overlooked.…”
Section: Discussionsupporting
confidence: 80%
“…With the help of observing real teaching/learning contexts and carrying out tasks under the supervision of university lecturers and cooperating teachers, pre-service teachers can develop their own teaching knowledge and skills and reflect on their beliefs (Tarman, 2012); this supports their cognitive learning and development (Cheng, Cheng, & Tang, 2010). Practicum is recognized as a learning arena where pre-service teachers maximize their opportunity to bridge theory with practice.…”
mentioning
confidence: 99%
“…To be trained as qualified teachers in pre-service education process, acquiring necessary knowledge, principles, attitudes and understandings related to their field of study and teaching profession is as important as gaining practical abilities or to be able to transform what they know into real learning-teaching situations. One of the most investigated issues in the studies conducted on teacher education is the gap between theory and practice (Allen & Wright, 2014; Allsopp, DeMarie, Alvarez Mchatton & Doone, 2006;Cheng, Cheng & Tang, 2010Hascher, Cocard & Moser, 2004;Korthagen & Kessels, 1999;Standal, Moen & Moe, 2014). Many teacher educators such as Carr (1987), Lenz Taguchi (2007 and Schön (2003) indicated that teaching is a profession in which theory and practice are embedded in each other; therefore separating theory from practice creates a false dichotomy (Cited in Allen, 2009).…”
Section: Purposementioning
confidence: 99%